Kohesi Gramatikal dan Leksikal dalam Cerpen Bahasa Inggris Berjudul “The Ant and the Dove” - Sari, Ni Made Dian Paramitha (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2026)
This study analyzes grammatical and lexical cohesion in the English short story entitled